Severe CMD with Novel Mutation in Lamin A/C Gene - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers at Queen Fabiola Children's University Hospital, Brussels, Belgium, report a 7-year-old Belgian boy with a 5 months-onset congenital muscular dystrophy and laminopathy caused by a de novo heterozygous LMNA gene mutation.